2003
DOI: 10.1002/jbm.a.10087
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface chemistry and nanotopography of titanium nitride (TiN) films on 3T3-L1 fibroblasts

Abstract: The cell-material interaction of 3T3-L1 fibroblasts with TiN films was studied in vitro. TiN films were deposited onto glass substrates to thicknesses of 0.2 and 1.0 microm by pulsed dc reactive magnetron sputtering. For comparison TiN films were deposited by closed field unbalanced magnetron sputter ion plating by Teer Coatings Ltd. (Hartlebury, UK) to result in TiN films with similar surface chemistries but having increased topographical features. TiN films were characterized using X-ray diffraction, X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…The XRD results were consistent with the results of Cyster et al [33] and Chien et al [17]. The peaks of TiN and TiAlN appeared at almost the same degree such as the (111) plane at 36.5, (200) plane at 42.6, (220) plane at 61.7 degrees.…”
Section: Scanning Electron Micrographs Of Tin and Tialn Coatingsupporting
confidence: 90%
See 3 more Smart Citations
“…The XRD results were consistent with the results of Cyster et al [33] and Chien et al [17]. The peaks of TiN and TiAlN appeared at almost the same degree such as the (111) plane at 36.5, (200) plane at 42.6, (220) plane at 61.7 degrees.…”
Section: Scanning Electron Micrographs Of Tin and Tialn Coatingsupporting
confidence: 90%
“…Compared to the ground surface (0.26 µm), the TiN and TiAlN coated surface showed rather smooth surface (0.03 µm by TiN and 0.02 µm by TiAlN) [17]. Cyster et al [33] reported the surface roughness of TiN films deposited by four different methods to be in the range of 1.0-5.6 nm. They measured the roughness by AFM.…”
Section: Scanning Electron Micrographs Of Tin and Tialn Coatingmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, stem cells can be stimulated by chemical or topographical cues (10). At the moment, it is believed that stem cells can sense and initiate an appropriate response to the physicochemical properties of their extracellular matrix (ECM) or any substrate that they are cultured on, by regulating their complex signaling pathways (11)(12)(13)(14)(15)(16). Cells are naturally located in a chemically and topographically complicated environment in vivo, which is different from what is used commonly for in vitro culture conditions (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%